PENDIDIKAN EMOSIONAL ANAK DALAM KELUARGA - Bermi, Wibawati (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
The family is an important position among social institutions that have concern for children. The family must be able to prepare a good generation for the future, because the family is a small scope that can bring someone a good social life. Good social order is influenced by family conditions. Society is a collection of reflections from the lifestyle, world view, even the perspective of each individual in the family. The family plays a very important role in directing children to become a generation of good morality and benefit the community.